The WNT signaling antagonist Dickkopf‐1 directs lineage commitment and promotes survival of the preimplantation embryo. Issue 9 (22nd May 2014) - Denicol, Anna C.; Block, Jeremy; Kelley, Dale E.; Pohler, Ky G.; Dobbs, Kyle B.; Mortensen, Christopher J.; Ortega, M. Sofia; Hansen, Peter J.
Abstract : Successful embryonic development is dependent on factors secreted by the reproductive tract. Dickkopf‐1 (DKK1), an antagonist of the wingless‐related mouse mammary tumor virus (WNT) signaling pathway, is one endometrial secretory protein potentially involved in maternal‐embryo communication. The purpose of this study was to investigate the roles of DKK1 in embryo cell fate decisions and competence to establish pregnancy. Using in vitro ‐produced bovine embryos, we demonstrate that exposure of embryos to DKK1 during the period of morula to blastocyst transition (between d 5 and 8 of development) promotes the first 2 cell fate decisions leading to increased differentiation of cells toward the trophectoderm and hypoblast lineages compared with that for control embryos treated with vehicle. Moreover, treatment of embryos with DKK1 or colony‐stimulating factor 2 (CSF2; an endometrial cytokine known to improve embryo development and pregnancy establishment) between d 5 and 7 of development improves embryo survival after transfer to recipients. Pregnancy success at d 32 of gestation was 27% for cows receiving control embryos treated with vehicle, 41% for cows receiving embryos treated with DKK1, and 39% for cows receiving embryos treated with CSF2. These novel findings represent the first evidence of a role for maternally derived WNT regulators during this period and could lead to improvements in assisted reproductive technologies.—Denicol, A. C., Block, J., Kelley, D. E., Pohler, K. G., Dobbs, K. B., Mortensen, C. J., Ortega, M. S., Hansen, P. J. The WNT signaling antagonist Dickkopf‐1 directs lineage commitment and promotes survival of the preim‐plantation embryo. FASEB J. 28, 3975‐3986 (2014). www.fasebj.org